Tug of war at the exit door. - Dustin, M; Chakraborty, A (2008)
The lipid sphingosine-1-phosphate has been identified as a key exit signal for lymph nodes. In this issue of Immunity, Pham et al. (2008) show that its action can only be understood in the context of retention signals transduced by CCR7.